Arthroscopic partial resection of the discoid meniscus in children - Atay, Özgür Ahmet; Doral, Mahmut Nedim; Aksoy, Mehmet Cemalettin; Tetik, Onur; Leblebicioğlu, Gürsel (The Turkish Journal of Pediatrics, 1997)
Thirteen children with 14 lateral discoid menisci were reviewed at an average follow-up of 2.7 years. Their average age at the time of the operation was 12.8 years. Most of the children had vague and intermittent painful symptoms, and the classical "clunk" was demonstrable in nine of the 13 patients in clinical examinations. Thirteen children underwent arthroscopic partial meniscectomy for symptomatic discoid lateral meniscus, by performing partial resection. This procedure, modifying the discoid lateral meniscus to the normal semilunar shape, was indicated only when the capsular attachment was intact.The results were excellent both clinically and radiologically. Furthermore, rehabilitation time was considerably shorter than the time required after open procedures.Arthroscopic discoid meniscus surgery performed by experienced and skilled hands gives better results. According to the literature and our experiences, it is better to perform open techniques in patients with stiff knees. Additionally, it is technically feasible to use small joint instruments in the pediatric age group.
Keywords: arthroscopy; discoid meniscus